2000
DOI: 10.1080/10473289.2000.10464168
|View full text |Cite
|
Sign up to set email alerts
|

Infant Mortality and Air Pollution: A Comprehensive Analysis of U.S. Data for 1990

Abstract: This paper uses U.S. linked birth and death records to explore associations between infant mortality and environmental factors, based on spatial relationships. The IMPLICATIONS Air pollution has been one of many suspected risk factors for SIDS, as well as for other causes of infant mortality. A previous epidemiologic study based on geographic gradients found a relationship between SIDS and PM 10 and speculated that fine particles (PM 2.5 ) might be the real culprit. However, U.S. data on SIDS clearly show a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 46 publications
3
78
3
2
Order By: Relevance
“…11 A second study found no increase in daily SO 2 levels on days of SIDS, compared with 1 and 2 weeks before and after, 12 whereas a third study reported a correlation between SIDS and elevated levels of gas pollutants (SO 2 , NO 2 , CO, and hydrocarbons) 7 weeks before the event. 13 Lipfert et al, 5 in reviewing their results and those of others, cautioned against attributing differences in SIDS rates to air pollution when there may be other observable but as yet unexplained differences between regions that influence mortality rates. The present report makes a significant contribution by confirming an adverse effect of air pollution in a large population study using a study design that is not confounded by differences among populations or geographic areas (a potential weakness of previous studies that compared regions).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 A second study found no increase in daily SO 2 levels on days of SIDS, compared with 1 and 2 weeks before and after, 12 whereas a third study reported a correlation between SIDS and elevated levels of gas pollutants (SO 2 , NO 2 , CO, and hydrocarbons) 7 weeks before the event. 13 Lipfert et al, 5 in reviewing their results and those of others, cautioned against attributing differences in SIDS rates to air pollution when there may be other observable but as yet unexplained differences between regions that influence mortality rates. The present report makes a significant contribution by confirming an adverse effect of air pollution in a large population study using a study design that is not confounded by differences among populations or geographic areas (a potential weakness of previous studies that compared regions).…”
Section: Discussionmentioning
confidence: 99%
“…SIDS rates were not adjusted for birth weight or income, and gaseous pollutants were not considered in the study. Another cross-sectional study, by Lipfert et al, 5 found an association between levels of particulates, but not gases, and SIDS incidence, with an unadjusted odds ratio of 1.42 (no confidence interval given) between metropolitan statistical areas with low versus high levels of PM 10 pollution (27.5 and 50.9 g/m 3 , respectively). This association persisted after adjustment for several factors including gender, ethnic background, birth weight, mother's aid, adequacy of prenatal care, smoking, and education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers are finding it worthwhile to investigate a link of PM 2.5 exposure with adverse birth outcomes, 21,22 epigenetic alteration, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] infant mortality, [37][38][39][40][41][42] athero sclerosis, [43][44][45] stroke, 46-50 rheumatic autoimmune diseases, 51,52 central nervous system disorders, [53][54][55][56][57] and diabetes. [58][59][60] Since many of these health conditions are interlinked, comprehensive studies are required to better understand the impact of PM 2.5 .…”
Section: Neurotoxic Effectsmentioning
confidence: 99%